Angle of Progression on Ultrasound in the Second Stage of Labor and Spontaneous Vaginal Delivery - Bibbo, Carolina; Rouse, Caroline E.; Cantonwine, David E.; Little, Sarah E.; McElrath, Thomas F.; Robinson, Julian N. (American Journal of Perinatology, 2018)
Objective The objective of this study was to assess the association between the angle of progression (AoP) measured by transperineal ultrasound and mode of delivery and duration of the second stage.Study Design This is a prospective observational study of nulliparous women with a singleton gestation at term in which serial transperineal ultrasound examinations were obtained during the second stage of labor. Multivariable logistic regression and adjusted survival models were used for the analysis.Results A total of 137 patients were included in the analysis and median AoP for the study group was 153 degrees. The adjusted odds ratio (aOR) of requiring an operative delivery was 2.6 times higher for those patients who had an AoP < 153 degrees and the aOR of requiring a cesarean delivery was almost six times higher when compared with those patients who had an AoP ≥ 153 degrees (95% confidence interval [CI]: 1.0, 6.2; p = 0.04; aOR: 5.8, 95% CI: 1.2–28.3; p = 0.03, respectively). Those patients with an AoP < 153 degrees were at a higher hazard of staying pregnant longer (adjusted hazard ratio: 1.8, 95% CI: 1.2–2.8, p = 0.005).Conclusion The AoP has the potential to predict spontaneous vaginal delivery and the duration of the second stage of labor which may be useful in counseling patients and managing their labor.
Keywords: angle of progression; operative delivery; second stage of labor; spontaneous vaginal delivery; transperineal ultrasound